Rational design of cannabinoid type-1 receptor allosteric modulators: Org27569 and PSNCBAM-1 hybrids. (1st July 2021) - Nguyen, Thuy; Gamage, Thomas F.; Decker, Ann M.; Finlay, David B.; Langston, Tiffany L.; Barrus, Daniel; Glass, Michelle; Harris, Danni L.; Zhang, Yanan
Graphical abstract: Abstract: Allosteric modulation offers an alternate approach to target the cannabinoid type-1 receptor (CB1 ) for therapeutic benefits. Examination of the two widely studied prototypic CB1 negative allosteric modulators (NAMs) Org27569 and PSNCBAM-1 revealed structural resemblance and similar structure–activity relationships (SARs). In silico docking and dynamics simulation studies using the crystal structure of CB1 co-bound with CP55, 940 and Org27569 suggested that Org27569 and PSNCBAM-1 occupied the same binding pocket and several common interactions were present in both series with the CB1 receptor. A new scaffold was therefore designed by merging the key structural features from the two series and the hybrids retained these binding features in the in silico docking studies. In addition, one such hybrid displayed similar functions to Org27569 in dynamic simulations by preserving a key R214 3.50 -D338 6.30 salt bridge and maintaining an antagonist-like Helix3-Helix6 interhelical distance. Based on these results, a series of hybrids were synthesized and assessed in calcium mobilization, [ 35 S]GTPγS binding and cAMP assays. Several compounds displayed comparable potencies to Org27569 and PSNCBAM-1 in these assays. This work offers new insight of the SAR requirement at the allosteric site of the CB1 receptor and provides a new scaffold that can be optimized for the development of future CB1 allosteric modulators.